2012
DOI: 10.1063/1.4707346
|View full text |Cite
|
Sign up to set email alerts
|

How does water-nanotube interaction influence water flow through the nanochannel?

Abstract: Water permeation across various nitrogen-doped double-walled carbon nanotubes (N-DWCNT) has been studied with molecular dynamics simulations to better understand the influence of water-nanopore interaction on the water permeation rate. There exists a threshold interaction energy at around -34.1 kJ/mol. Over the threshold energy, the water flow through N-DWCNT decreases monotonically with the strengthening of the water-nanotube interaction. The effect on the water flow across the channel is found to be negligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
0
8
0
2
Order By: Relevance
“…The study on the flow of water across nanochannels or microchannels has many applications, e.g., for understanding biological activities [1][2][3][4][5][6][7][8], for designing nanodevices or nanomachines [6,[9][10][11], and even for studying the coalescence of Pickering emulsion droplets [12]. For example, it was found that the measured water flow across nanotubes exceeded values calculated from continuum hydrodynamics models by more than three orders of magnitude and that water permeation abilities of these nanotube-based membranes were several orders of magnitude higher than those of commercial polycarbonate membranes [13].…”
Section: Introductionmentioning
confidence: 99%
“…The study on the flow of water across nanochannels or microchannels has many applications, e.g., for understanding biological activities [1][2][3][4][5][6][7][8], for designing nanodevices or nanomachines [6,[9][10][11], and even for studying the coalescence of Pickering emulsion droplets [12]. For example, it was found that the measured water flow across nanotubes exceeded values calculated from continuum hydrodynamics models by more than three orders of magnitude and that water permeation abilities of these nanotube-based membranes were several orders of magnitude higher than those of commercial polycarbonate membranes [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that when confined in nanochannels with sizes ranging from sub-nanometer to several nanometers, fluids can exercise unconventional and sometimes even counterintuitive behaviors121314151617. Such behaviors are mainly due to the fact that the interactions among the fluid ions or molecules change dramatically when they are in close contact with the confining walls1518. Both molecular simulations and experimental works have revealed that the flow rate of water through a few layered GE is orders of magnitude higher than that predicted by the conventional Hagen-Poiseuille law71419.…”
mentioning
confidence: 99%
“…In order to understand those different behaviours, as Li et al [31] pointed out that the van der Walls interaction is much stronger than the electrostatic interaction energy. Thus, we calculate the interactions potential of van der Waals between water molecules in SWCNT A and the carbon atoms along the centre of SWCNT A axes.…”
Section: Resultsmentioning
confidence: 98%